Antagonistic activities of coagulase-positive staphylococci - Balusek, J; Hájek, V (Journal of hygiene, epidemiology, microbiology, and immunology, 1985)
Antagonistic activities were investigated by Frédérioq's plate method in 1,014 coagulase-positive staphylococcal strains of different species and origins. Staphylococcin effect was demonstrated in 12 (2%) of the 559 Staphylococcus aureus strains, in 51 (18%) of the 283 S. intermedius strains, and in 1 (3%) of the 36 S. hyicus subsp. chromogenes strains. Lysostaphin was identified in the 15 (5%) S. intermedius strains. In addition, heat-stable bacteriostatic agent was detected in 45 (33%) and heat-labile bacteriolytic agent in 7 (5%) of the 136 S. hyicus subsp. hyicus strains. An attempt was made at antagonistic activity typing in all of the active staphylococcal strains.
Keywords: Rabbits; Bacteriocins; teplota; Humans; skot; Dogs; Staphylococcus aureus; zvířata; psi; bakteriociny; Cattle; lysostafin; koagulasa; Staphylococcus; Animals; lidé; králíci; Lysostaphin; Coagulase; Temperature